Metagenomic Analysis of Intestinal Microbiota Derived from Stool Samples of Third-Trimester Pregnant Women - Kamaruddin, Mudyawati; Zamzam, Miftahul Khairiyah; Pratama, Rahadian; Nur, AbdurRahman Shakhr; Muthiadin, Cut; Sembiring, Christine; Triananinsi, Nurhidayat; Nurisyah, Nurisyah; Dewi, Ratnasari; Fatmawati, Fatmawati; Erniawati, Erniawati; Jusni, Jusni; Basmiati, Basmiati (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2025)
Background: The human gut microbiota plays a unique role in metabolism, immunity, and nutrient absorption.  Various studies on the gut microbiota have identified a link between changes in bacterial abundance in the gut known as dysbiosis (imbalance) and the pathogenesis of certain disorders. It is known that an imbalance in the ratio of the phyla Firmicutes and Bacteroidetes has been associated with various chronic diseases, including inflammatory bowel disease and metabolic disorders. The Firmicutes/Bacteroidetes (F/B) ratio is a measure used to assess gut microbiota composition, which is believed to play a significant role in intestinal health and metabolism. Studies suggest that a higher F/B ratio is often associated with obesity and other metabolic conditions. Objective: This study aims to carry out metagenomic analysis of third-trimester pregnant women's faecal samples to predict degenerative diseases using third-generation whole genome sequencing, namely PromethION nanopore technology.  Method: Nanopore Technology: DNA sequencing of faecal samples from pregnant women in the third trimester was performed using the Oxford Nanopore Technology (ONT) device based on the Ligation Sequencing gDNA - Native Barcoding Kit 24 V14 and following its guidelines. Result: Based on the quality and quantity of total DNA reads from 20 stool samples from pregnant women, only 4 samples were continued for analysis (1A, 2A, 3A and 4A). The results of the abundance of intestinal microbiota based on the most abundant phylum are Proteobacteria, Bacteriodetes, and Firmicutes. Conclusion: Meanwhile, based on species abundance, it shows that Prevotella copri (phylum Bacteriodetes) is abundant in samples 2A, 3A and 4A, while in sample 1A the most abundant species is Succinivirio dextrinosolvens (phylum Proteobacteria). Bacteroidetes are a group of Gram-negative bacteria that are often found to increase in individuals with type 2 diabetes and obesity